Belt and Road Initiative (BRI) In Islamic Economics Distribution Perspective - Efni Anita; Eja Armaz Hardi (Al-Amwal : Jurnal Ekonomi dan Perbankan Syari'ah, 2020)
This article aims to analyse Indonesia's policy of joining China's Belt and Road Initiative (BRI) through a perspective of distribution in Islamic economics. The BRI project is one of the agendas of the Chinese government to expand economic hegemony in the international market. At the same time, the Indonesian government has a national development priority program (PSN). However, the state's finite financial condition and the stagnation of economic growth became an obstacle for the Indonesian government to realize the domestic infrastructure projects. Therefore, the Indonesian government requires a source of capital other than the state budget. One of the steps taken by the Indonesian government is to become part of BRI. Behalf of these difficulties and opportunities, how Islamic economics argue the Indonesian government policy especially on distribution perspective. To address the question, this article utilizes descriptive qualitative methods and the theory of distribution of Islamic economics. It was found that the Indonesian government's infrastructure policy is in line with the spirit of Islamic distribution to reduce income disparity by providing equal access to infrastructure for the communities. Beside BRI's open access and integration to regional countries and supported by the needs of China's domestic industrial raw materials, Indonesia is predicted to be the largest exporter of raw materials. The need to export these raw materials will also tend to be exploitative and contrary to Islamic principles. Therefore, to tackle that, this article recommends the formulation of policies that encourage an expansive domestic industry so that Indonesia is not only an exporter of raw materials but also an exporter of goods and services.